Western architectural influences in the Court of Siam 1851-1925 : a thesis presented in fulfilment of the requirements for the degree of Master of Design, Massey University, Wellington, New Zealand - Khwanphulsri, Eakawin (Massey University, 2001)
This thesis examines the use of Western architecture in the design of the permanent and summer palaces of King Rama IV, King Rama V and King Rama VI of Thailand. It is a study of the use of interior spaces, and how the Kings and their families responded to their adapted Western interior environments, and how they maintained traditional ideas and practices in their daily lifestyles between 1851 and 1925. The story by Anna Leonowens – The King and I; is a popular account of how The Court of Siam responded to Western influences. In the novel, the story (although particular contents were fabricated) explained that King Rama IV took on the fundamental concepts of Western lifestyle and etiquette, and emphasised these with the use of Western architecture. He built a summer palace with interiors based on traditional and Western styles. The palace was used for relaxation and for accommodating foreign diplomats. His acceptance of Western ideals later influenced his children's lifestyles, particularly that of King Rama V. King Rama V maintained the significance of Western ideals in his palaces, and was even more enthusiastic than his father about Western influences. King Rama VI's personal lifestyle, however, was based on traditional ideals rather than Western rituals. His residences were designed in a different manner from his father's palaces. These differences indicate that each King had their own approaches on the maintenance of Western ideas and practices. The thesis focuses on the relationships between the use of different architectural styles for the interior design of individual palaces, and the adaptation and utilisation of interior space by the residents in order to fulfil social and political events, as well as their daily domestic rituals.
Keywords: Thailand Palaces; Thailand Architecture